Emerging antibodies for the treatment of multiple myeloma - Zagouri, F.; Terpos, E.; Kastritis, E.; Dimopoulos, M.A. (Expert Opinion on Emerging Drugs, 2016)
ABSTRACT: Introduction: Monoclonal antibodies mark the beginning of a new era in the context of multiple myeloma (MM) treatment. Numerous antibodies have been tested or are currently in development for patients with MM, in order to improve tolerability and quality of life. Areas covered: This manuscript reviews emerging antibodies for the treatment of MM i.e. elotuzumab, daratumumab, MOR03087, isatuximab, bevacizumab, cetuximab, siltuximab, tocilizumab, elsilimomab, azintrel, rituximab, tositumomab, milatuzumab, lucatumumab, dacetuzumab, figitumumab, dalotuzumab, AVE1642, tabalumab, pembrolizumab, pidilizumab, nivolumab. Expert opinion: Amongst these antibodies, elotuzumab which targets SLAMF-7 and daratumumab which targets CD38, have been recently approved by FDA for patients with relapsed/refractory MM. Both agents are well tolerated. Multiple clinical trials incorporating these monoclonal antibodies in MM treatment are currently ongoing. Of special interest are the anticipated results of phase III clinical trials with elotuzumab [NCT0189164; NCT01335399; NCT02495922] and daratumumab [NCT02252172; NCT02195479] in newly diagnosed MM patients. Moreover, of great interest are the awaited data on pembrolizumabin combination with pomalidomide and dexamethasone in refractory/relapsed MM patients [NCT02576977] and in combination with lenalidomide and dexamethasone in newly diagnosed MM patients. It seems that the incorporation of monoclonal antibodies will change the landscape of myeloma therapy in the near future. © 2016 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Daratumumab; Elotuzumab; monoclonal antibodies; multiple myeloma; targeted therapy